UPAYA PENINJAUAN KEMBALI PERKARA KEPAILITAN TENTANG PEMBATALAN HOMOLOGASI (Tinjauan Yuridis Putusan Nomor 1/Pdt.Sus.Pembatalan Perdamaian/2018/PN Niaga Sby Jo Putusan Nomor 43 PK/Pdt.Sus-Pailit/2019) - Nurul Alfaruni Safitri; Rahadi Wasi Bintoro; Mr Sanyoto (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Article 293 of the Bankruptcy and PKPU Law regulating open remedies for PKPUdecisions only applies to PKPU termination decisions. Decision Number 1/Pdt.Sus. Pembatalan Perdamaian /2018/PN.Niaga.Sby submitted by former employees of debtors in the form of BUMN. The petition was granted by the Surabaya Commercial Court Judge Panel. Based on the decision to cancel the homologation, the debtor submits a legal review to the Supreme Court, but the Supreme Court in its decision stated that the request for legal remedy was not acceptable. The purpose of this study was to determine the legal remedies submitted in accordance with the Bankruptcy and PKPU Law and to determine the ratio of decidendi of the Surabaya Commercial Court Judges in applying the legal standing of the applicant in the request to cancel the homologation. The method used is normative juridical. Based on data from the research results, it was found that the legal remedies submitted were not in accordance with the Bankruptcy and PKPU Law, because the court's decision regarding PKPU was not open to any legal remedies, unless otherwise stipulated in this Law. However, those exceptions do not include homologation cancellation decisions. The Panel of Judges for review was appropriate in applying the law because it was based on the provisions of Article 293 in conjunction with Article 290 of the Bankruptcy and PKPU Law which stipulates that no legal remedies are open to PKPU decisions. The decidendi ratio of the Surabaya Commercial Court Judge Panel is correct, the applicant has the capacity and legal standing to submit an application because the debtor is a BUMN in the form of a Persero. Therefore, advocates as attorneys should pay more attention to and understand the provisions in the Bankruptcy Law and PKPU, so there is no error in the submission of an application. Keywords: Legal Remedies, Bankruptcy, Homologation Cancellation.